2018
DOI: 10.1080/21501203.2018.1477849
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza fungi increased the susceptibility ofAstragalus adsurgensto powdery mildew caused byErysiphe pisi

Abstract: Powdery mildew caused by Erysiphe pisi is a major factor that affects the growth of standing milkvetch (Astragalus adsurgens). As arbuscular mycorrhizal fungi (AMF) have shown to be enhancing the resistance of plants to biotrophic pathogens such as powdery mildew, a study was carried out to look at the effects of three AMF, either singularly or in combination, on the growth of standing milkvetch and susceptibility to E. pisi. The results showed that the presence of AMF enhanced the growth of standing milkvetch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In addition, some research pointed out a higher protector effect of F. mosseae in comparison to other AMF species [ 61 , 62 ]. However, some studies reported higher severity of symptoms caused by viruses [ 35 , 63 ] or fungi disease [ 64 ], on leaves of mycorrhizal plants compared to non-mycorrhizal control plants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some research pointed out a higher protector effect of F. mosseae in comparison to other AMF species [ 61 , 62 ]. However, some studies reported higher severity of symptoms caused by viruses [ 35 , 63 ] or fungi disease [ 64 ], on leaves of mycorrhizal plants compared to non-mycorrhizal control plants.…”
Section: Discussionmentioning
confidence: 99%
“…did not demonstrate an increased resistance to powdery mildew [ 97 ], and standing milkvetch ( Astragalus adsurgens Torr.) became even more susceptible to the disease when mycorrhized [ 98 ]. Taking all of the above into account, mycorrhiza undoubtedly benefits the plant, but it cannot be considered as the main and universal method of protection against powdery mildew.…”
Section: The Art Of Warmentioning
confidence: 99%
“…The herbaceous species of Astragalus are annuals or perennials, and the shrubs are perennials. Astragalus species have been reported to be mycorrhizal (Rose, 1981;Zhao et al, 1997;Barroetavena et al, 1998;Shi et al, 2006;Tian et al, 2006;Bai et al, 2009;Liu et al, 2018) and to fix nitrogen (Wilson & Chin, 1947;Looman, 1974;Shearer et al, 1983;Baskin & Baskin, 1989b;Faria et al, 1989;Murooka et al, 1993;Evans and Ehleringer, 1994;Gibson et al, 1998;Gao et al, 2001;Meinke et al, 2013).…”
Section: Life Cycle and Life Formmentioning
confidence: 99%